About the child’s right to establish its origins on the mother’s part - Sobas, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
This text is about the child’s right to determine its genetic origin in the field of establishing motherhood, also in relation to the problem of medically assisted procreation techniques and the so-called ‘surrogate motherhood’. Undertaking this subject is an answer to faster-growing science and medicine. It is also an attempt to compare legal provisions with the views of representatives of the doctrine as well as everyday life in relation to the right to determine origins.